2015
DOI: 10.18632/oncotarget.5335
|View full text |Cite
|
Sign up to set email alerts
|

LYAR promotes colorectal cancer cell mobility by activating galectin-1 expression

Abstract: Colorectal cancer (CRC) is one of the leading causes of cancer-related death worldwide. However, the molecular mechanisms of CRC pathogenesis are not fully understood. In this study, we report the characterization of LYAR (Ly-1 antibody reactive clone) as a key regulator of the migration and invasion of human CRC cells. Immunohistochemistry analysis demonstrated that LYAR is expressed at a higher level in metastatic CRC tissues. We found that LYAR promoted the migratory and invasive capabilities of CRC cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…For C06 in particular, the top five differentially expressed (DE) genes (ranked on p-value) were CCL5, GZMK, CXCR3, LYAR, and NKG7 ( Supplementary Table S2), as shown in the UMAP plots colored by relative expression ( Figure 2C). CXCR3, CCL5, and NKG7 have all been associated previously with T H 1 migratory capacity (55,56) and phenotype (57), while the expression of GZMK and LYAR likely indicate a cytotoxic and activated population (58,59). Figure 2C also depicts the canonical Treg markers, FOXP3 and IKZF2, which were highly expressed in the majority of APB and CB Treg clusters but only lowly expressed in C06.…”
Section: Scrna-seq Identifies Contaminants In Pre-expanded Tregsmentioning
confidence: 59%
“…For C06 in particular, the top five differentially expressed (DE) genes (ranked on p-value) were CCL5, GZMK, CXCR3, LYAR, and NKG7 ( Supplementary Table S2), as shown in the UMAP plots colored by relative expression ( Figure 2C). CXCR3, CCL5, and NKG7 have all been associated previously with T H 1 migratory capacity (55,56) and phenotype (57), while the expression of GZMK and LYAR likely indicate a cytotoxic and activated population (58,59). Figure 2C also depicts the canonical Treg markers, FOXP3 and IKZF2, which were highly expressed in the majority of APB and CB Treg clusters but only lowly expressed in C06.…”
Section: Scrna-seq Identifies Contaminants In Pre-expanded Tregsmentioning
confidence: 59%
“…On the other hand, the expression of NF-B-regulated proinflammatory cytokines, including IL-6, IL-8, IL-1␤, and TNF-␣ are also inhibited by LYAR, and LYAR inhibits the NF-B promoter activity, suggesting that LYAR may participate in the NF-B signaling pathway, thus regulating cellular inflammatory responses, and further investigations would benefit for a comprehensive understanding of LYAR's role in innate immunity. LYAR is a transcription factor, and two zinc finger DNA binding motifs in its N-terminal domain are regarded to be involved in transcriptional regulation (26,31,32). This raises the concern that the inhibitory activity of LYAR in antiviral gene expression might be an effect of its transcriptional repression of those genes.…”
Section: Discussionmentioning
confidence: 99%
“…GPR64 is known to be involved in the adhesion and migration of breast cancer cells through mechanisms including a noncanonical NFkB pathway . Furthermore, it was reported that transcription factor LYAR promote tumor cell migration and invasion by upregulating galectin‐1 gene expression in colorectal cancer . Another interesting network link was RFC5 (activated by TRPS1 in B42‐11 and B42‐16) as it appeared in many (10 out of 14) pathways related to DNA repair and cell cycle/mitosis from the differential expression analysis and is among the top five genes correlating with TRPS1.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, it was reported that transcription factor LYAR promote tumor cell migration and invasion by upregulating galectin-1 gene expression in colorectal cancer. 40 Another interesting network link was RFC5 (activated by TRPS1 in B42-11 and B42-16) as it appeared in many (10 out of 14) pathways related to DNA repair and cell cycle/mitosis from the differential expression analysis and is among the top five genes correlating with TRPS1. The RFC5 gene belongs to the replication factor C family and was described to reflect the hallmark of cancer "genomic instability."…”
Section: Discussionmentioning
confidence: 99%